Analisis Pengaruh Kepatuhan Dan Sanksi Pajak Terhadap Tingkat Penerimaan PPh Orang Pribadi - Hutama, Feky Satrya; Padmono, Yazid Yud (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to analyze and test the compliance of taxpayers and tax sanction to the Income tax revenue level (PPh) at KPP Pratama Surabaya Sawahan. The data collection technique is carriedout by issuing questionnaire. The data is primary data which which has been collected by issuing questionaires to the repondents. Quantitative methods is used as the methods of research whereas multiple linier regressions are used as the analysis techniques. The compliance of tax payers is the obidians of the tax payers in carrying of sanction is the guarantee that the provision of the tax regulation (Taxation norms). Will be complied / obeyed. Income tax is a tax that is levied on person an entities accordance with the income that has been obtained in one year. This research show that: (1) the compliance of thax payers has signifikan influence to the level of income tax revenue (PPh) at KPP Pratama Surabaya Sawahan. (2) the tax sanction has sinifikan in fluence to the revenue level of income tax (PPh) at KPP pratama Surabaya SawahanKeywords: The compliance of taxpayer, Tax sanction, and Income tax